Strategies for call admission control in integrated services wireless mobile networks - Mohamed, Nagla Osman; Deniz, Derviş Z. (My University, 2006)
Call admission control (CAC) and its effects on quality of service (QoS) for integrated services wireless networks are studied. A wireless cell with m channels is considered. The cell serves three different types of calls; types 1, 2 and 3, corresponding to voice, data and video services respectively. Type i calls require bi channels for their service. The wireless cell serves newly arriving as well as handoff customers from nearby cells. A novel CAC strategy named Guard Channels with Threshold Strategy (GCTS) is proposed, the system is modeled and its performance is evaluated using simulation. This system is compared with the well known Guard Channels Strategy (GCS). It is observed that in the case of the guard channels strategy, newly arriving or handoff calls with large bandwidth requirements are blocked more. This unfairness in the guard channels strategy is alleviated to a great extent by the guard channels strategy with thresholds. It is shown that the desired performance results can be obtained at the cost of reduced system utilization. © 2006 IEEE.
3rd International Symposium on Wireless Communication Systems 2006, ISWCS'06 --
Keywords: Cac; Handoff; Integrated services; Mobile networks; Wireless